Health care professionals from developing countries report educational benefits after an online diabetes course - Nicolai J. Wewer Albrechtsen; Kristina W. Poulsen; Lærke Ø. Svensson; Lasse Jensen; Jens J. Holst; Signe S. Torekov (BMC Medical Education, 2017)
Abstract Background Medical education is a cornerstone in the global combat against diseases such as diabetes and obesity which together affect more than 500 million humans. Massive Open Online Courses (MOOCs) are educational tools for institutions to teach and share their research worldwide. Currently, millions of people have participated in evidence-based MOOCs, however educational and professional benefit(s) for course participants of such initiatives have not been addressed sufficiently. We therefore investigated if participation in a 6 week open online course in the prevention and treatment of diabetes and obesity had any impact on the knowledge, skills, and career of health care professionals contrasting participants from developing countries versus developed countries. Methods 52.006 participants signed up and 29.469 participants were active in one of the three sessions (2014–2015) of Diabetes - a Global Challenge. Using an online based questionnaire (nine sections) software (Survey Monkey), email invitations were send out using a Coursera based database to the 29.469 course participants. Responses were analyzed and stratified, according to the United Nations stratification method, by developing and developed countries. Results 1.303 (4.4%) of the 29.469 completed the questionnaire. 845 of the 1303 were defined as health care professionals, including medical doctors (34%), researchers (15%), nurses (11%) and medical students (8%). Over 80% of the health care participants report educational benefits, improved knowledge about the prevention and treatment therapies of diabetes and furthermore improved professional life and practice. Over 40% reported that their professional network expanded after course participation. Study participants who did not complete all modules of the course reported similar impact as the ones that completed the entire course(P = 0.9). Participants from developing countries gained more impact on their clinical practice (94%) compared to health care professionals from developed regions (88%) (Mean of differences = 6%, P = 0.03. Conclusions Based on self-reports from course participants, MOOC based medical education seems promising with respect to providing accessible and free research-based education to health professionals in both developing and developed countries. Course participants from developing countries report more benefits from course participation than their counterparts in the developed world.